A fluorescent probe bearing two reactive groups discriminates between fluoride-containing G series and sulfur-containing V series nerve agents. Issue 16 (6th July 2020) - Weihui, Wu; Shaohui, Sui; Jian, Li; Liang, Zong; Dan, Li; Yanhua, Xiao; Lianyuan, Wang; Haiyan, Zhu; Yonglin, Shen; Zhigang, Jiang
Abstract : A fluorescent probe bearing two functional groups was designed to discriminate fluoride-containing G and sulfur-containing V series nerve agents through reacting with fluorides and thiols, which exhibited obvious and diverse fluorescence changes. Abstract : Herein, we present an approach to design a fluorescent molecule for detection and discrimination of fluoride-containing G series and sulfur-containing V series nerve agents. FP1 bearing two reactive groups can react with fluorides and thiols from the two types of nerve agents and generate different products with obvious and diverse fluorescences, which will be helpful when dealing with terrorist crises.